Melampaui Kepatuhan Semu: Rekonstruksi Pembelajaran Pendidikan Agama Islam melalui Pedagogi Jurnal Reflektif dalam Internalisasi Karakter Religius - Rifqi Fathan Saepudin Muzakki; Aceng Kosasih; Saepul Anwar (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
Evaluation of Islamic Religious Education (PAI) in formal schools is often reduced to a behavioristic checklist instrument that triggers the pathology of pseudo-compliance. This practice gives rise to cognitive objectivation, social desirability bias, and relational alienation, where students obey purely because of institutional supervision, not a sense of faith. This study aims to uncover this pathology and reconstruct PAI learning through the application of reflective journal pedagogy as an instrument for internalizing students' religious character. The method used is qualitative with a Holistic Single Case Study design that is evaluative and exploratory, taking the locus at SMPN 23 Bandung. The study population involved 30 8th-grade students for the longitudinal macro analysis, with 7 samples drawn using purposive maximum variation for the micro phenomenological analysis. The reflective journal instrument was operationalized for four weeks, strengthened by in-depth interviews and triangulation with PAI teachers and guidance counselors. The results of the study indicate a dramatic shift in the distribution of the depth of reflection of the class population: the proportion of students at the Descriptive Writing level decreased from 63% to 7%, while 17% of students successfully achieved Critical Reflection. Inductive thematic extraction resulted in eight dominant character values ​​born from the sociological crisis of adolescence: Honesty (Shidq), Trustworthiness, Sincerity, Patience (Shabr), Repentance (Tawakkal), Gratitude (Shukr), Responsibility (Masuliyyah), and Birrul Walidain. This study concludes that Al-Ghazali's triadic convergence ('Ilm, Hal, 'Amal) is the missing link in the evaluation of Islamic Religious Education (PAI), where the inner state (Hal) acts as an absolute catalyst before authentic moral action ('Amal) can be realized. Reflective journals are proven to be able to restore the essence of Islamic Religious Education from administrative routines to living inner laboratories.